Arrangements of arbitrary constructions and interaction of urban and urban planning law provisions - Kopsidas, Odysseas (Edelweiss Applied Science and Technology, 2024)
The study explores the challenges bobbing up from the proliferation of arbitrary structures in city settings, tracing their historical roots to pre- and submit-struggle durations. Fueled by socio-financial factors and a lack of strong housing policies, arbitrary creation has become deeply ingrained, posing significant social and environmental worries. Departing from traditional views, the paper severely examines the intersection of arbitrary creation provisions with co-possession issues, emphasizing the want for comprehensive regulation. The look investigates the long-term evolution of laws governing co-owned freeholds, delving into the complex interaction among civil law, ceiling ownership, and freehold guidelines. This essay examines arbitrary buildings via analyzing the felony framework and jurisprudence, addressing challenges in co-possession and holiday domestic land acquisition. The legislative evolution, from the twenties to trendy regulations, goals to stability historical maintenance with city development. Recent legislative adjustments have simplified processes and resolved controversies in co-ownership and arbitrary production issues.